2015
DOI: 10.1007/s11164-015-2267-z
|View full text |Cite
|
Sign up to set email alerts
|

An efficient synthesis of anti-microbial 1,2,4-triazole-3-thiones promoted by acidic ionic liquid

Abstract: Acidic ionic liquid, [(Py) 2 SO][HSO 4 ] 2 has been used as an efficient catalyst for the reaction of ketone with thiosemicarbazide in ethanol at room temperature for the eco-friendly synthesis of spiro-1,2,4-triazolidine-3-thiones. Smooth reactions, ambient temperature, use of alcohol as a solvent, high yields, easy workup procedure and excellent recyclability of ionic liquid and high atom economy are the auxiliary advantages of the present protocol, which makes it ecofriendly. All the synthesized 1,2,4-trioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The reaction of oxadiazoles 9a-c with hydrazine hydrate in ethanol afforded 4-amino-5-aryl-1,2,4-triazole-3-thiones 10a-c (Scheme 1) [22]. Triazolethione-thiols ( Figure 4) have gained considerable importance in medicinal chemistry due to their potential anticancer [24,25], antimicrobial [26], antioxidant, antitumor [27], anti-tuberculosis [28], anticonvulsant [29], fungicidal [30], antiepileptic [31] and anti-inflammatory [32] activities. Triazolethione-thiols ( Figure 4) have gained considerable importance in medicinal chemistry due to their potential anticancer [24,25], antimicrobial [26], antioxidant, antitumor [27], antituberculosis [28], anticonvulsant [29], fungicidal [30], antiepileptic [31] and anti-inflammatory [32] activities.…”
Section: Synthesis Of 124-triazole-3-thionesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of oxadiazoles 9a-c with hydrazine hydrate in ethanol afforded 4-amino-5-aryl-1,2,4-triazole-3-thiones 10a-c (Scheme 1) [22]. Triazolethione-thiols ( Figure 4) have gained considerable importance in medicinal chemistry due to their potential anticancer [24,25], antimicrobial [26], antioxidant, antitumor [27], anti-tuberculosis [28], anticonvulsant [29], fungicidal [30], antiepileptic [31] and anti-inflammatory [32] activities. Triazolethione-thiols ( Figure 4) have gained considerable importance in medicinal chemistry due to their potential anticancer [24,25], antimicrobial [26], antioxidant, antitumor [27], antituberculosis [28], anticonvulsant [29], fungicidal [30], antiepileptic [31] and anti-inflammatory [32] activities.…”
Section: Synthesis Of 124-triazole-3-thionesmentioning
confidence: 99%
“…Patil et al [32] reported the synthesis of a series of spiro-1,2,4-triazole-3-thiones 169a-g varied from good to excellent yields (55-95%) from thiosemicarbazide (20) and different cyclic ketones using different catalysts, the most effective catalyst was 1,1 -sulfinyldipyridinium bis(hydrogen sulfate) ionic liquid which gave high yield and short reaction time in alcohol at room temperature (Scheme 46). Patil et al [32] reported the synthesis of a series of spiro-1,2,4-triazole-3-thiones 169a-g varied from good to excellent yields (55-95%) from thiosemicarbazide (20) and different cyclic ketones using different catalysts, the most effective catalyst was 1,1′-sulfinyldipyridinium bis(hydrogen sulfate) ionic liquid which gave high yield and short reaction time in alcohol at room temperature (Scheme 46). Patil et al [32] reported the synthesis of a series of spiro-1,2,4-triazole-3-thiones 169a-g varied from good to excellent yields (55-95%) from thiosemicarbazide (20) and different cyclic ketones using different catalysts, the most effective catalyst was 1,1′-sulfinyldipyridinium bis(hydrogen sulfate) ionic liquid which gave high yield and short reaction time in alcohol at room temperature (Scheme 46).…”
Section: Synthesis Of Spiro-124-triazolethionesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4-Triazolthione derivatives have been prepared successfully by various methods. The most common classical method is the dehydrative cyclization of different hydrazinecarbothioamides in the presence of basic media using various reagents such as sodium hydroxide [43], potassium hydroxide [44], sodium bicarbonate [45], and besides that, the acidic ionic liquid condition can be used for such cyclization followed by neutralization [46].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the diverse applications of 1,2,4‐triazole and its synthetic congeners, a plethora of methods have been reported for their synthesis . Amongst these, the simplest approach for the synthesis of 1,2,4‐triazolidine‐3‐thiones involves the reaction of aldehydes or ketones with thiosemicarbazides in the presence of catalysts such as sulfamic acid, N,N‐dimethylpyridine‐4‐amine, [C 16 MPy]AlCl 3 Br, [(Py) 2 SO][HSO 4 ], [HMPBSA]HSO 4 , glycine nitrate . Moreover, organic solvents like PEG‐400, glycerol and ethanol endorsing catalyst free conditions have also been reported.…”
Section: Introductionmentioning
confidence: 99%